1989
DOI: 10.1093/jac/24.suppl_a.265
|View full text |Cite
|
Sign up to set email alerts
|

The disposition and metabolism of meropenem in laboratory animals and man

Abstract: The disposition and metabolism of meropenem were studied in rats, dogs and cynomolgus monkeys following intravenous administration of [14C]-meropenem, and also in man following intravenous infusion of meropenem. Following intravenous administration to rats and dogs, radioactive material was very rapidly and widely distributed in the tissues, with highest levels detected in the kidney and other highly perfused organs. Concentrations in all tissues decreased rapidly with time. The plasma elimination half-life of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 0 publications
3
33
0
Order By: Relevance
“…A validated, reversephase high-performance liquid chromatography (HPLC) procedure was used to determine the concentration of meropenem in plasma (11). The assay is based on a solid-phase extraction that is followed by reverse-phase chromatography with UV detection at 296 nm.…”
Section: Methodsmentioning
confidence: 99%
“…A validated, reversephase high-performance liquid chromatography (HPLC) procedure was used to determine the concentration of meropenem in plasma (11). The assay is based on a solid-phase extraction that is followed by reverse-phase chromatography with UV detection at 296 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Studies with rats have shown that DHP-I activity in the brain is negligible (33), approximately 6.4-and 3,000-fold less than in the muscle and the lungs, respectively (17). Since the fraction of cilastatin (16 to 66%) that reaches the cerebrospinal fluid (CSF) is about 3-fold that of meropenem (6 to 20%) in mammals with inflamed meninges (34)(35)(36)(37)(38), the site of infection in this model would have increased M:C ratios with respect to the actual proportions injected subcutaneously. It provides greater protection of meropenem without further increasing the dose of cilastatin and, therefore, is a more sensible model to determine therapeutic equivalence with the mouse.…”
Section: Neutropenic Guinea Pig Soleus Infection Model (Sepsis By Thementioning
confidence: 99%
“…The drawback of MEM-CLA is that it requires intravenous access. The advantages are tolerable side effects (31), low plasma protein binding (32), and good lung penetration (33).…”
mentioning
confidence: 99%